Mothers' Perceptions on the Impact of Early Childhood Development and Parenting: A Comparative Study of Screen Time Groups in Indonesia - Vivi Irzalinda; Melly Latifah; Dwi Hastuti (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The increased use of digital devices during childhood, both in urban and rural areas with high technology access, raises concerns about their impact on child development and health. This calls for evidence-based interventions that consider the balance between the benefits and risks of screen time. However, existing empirical evidence shows inconsistencies in linking screen time duration to sociodemographic factors, parenting practices, and various aspects of child development. This study comparative analyses sociodemographic variables, parenting practices, and maternal perceptions in relation to screen time.' Methods: This cross-sectional study included 301 mothers of children aged 4-7 years in Bandar Lampung, Indonesia, using purposive sampling. A comparative analysis was conducted between the two groups based on screen time intensity. Ethical approval was obtained from the University Research Ethics Committee. The parenting practice instrument uses ‘Parenting SOS’ from Neshteruk, which has been modified and adapted. The screen time instrument and mothers' perceptions of the impact of child development use questionnaires from Rahmawati and Latifah, adapted and modified from Lauricella and Nikken & Schols. Statistical analyses (t-tests) compared key variables across screen time groups. Results: Results showed that mothers (p=0.012) and fathers (p=0.020) in the low screen time group were significantly older, with more consistent parenting practices in terms of behavior control (p=0.005), monitoring (p=0.016), and positive modelling (p=0.006). Meanwhile, children in the high screen time group were more frequently exposed to television (p=0.045) and diverse digital content (p=0.012). The low screen time group also tended to have higher child development scores (67.2%) than the high screen time group (63.9%). The low screen time group had better maternal perceptions of the impact of gadgets on child development than the high screen time group (p=0.046). Conclusion: This study contributes to family systems theory by identifying maternal age and parenting consistency as buffers against excessive screen time, and provides comparative evidence from Indonesia's urban-rural context. Findings support targeted parenting programs and age-appropriate content policies. This study makes a contextual contribution to the global literature through the local Indonesian context while supporting the development of culturally adaptive public health strategies.